Sejarah Islam Nusantara: Awal mula masuknya Islam di Indonesia - Fatih, Muhammad Al (Maliki Interdisciplinary Journal, 2024)
The history of Islam in the archipelago is a complex and rich narrative, covering a time span of more than a thousand years and involving various social, political and cultural actors and dynamics. The process of Islamization in the archipelago began around the 13th century, through trade interactions between Muslim traders from Arabia, Persia, India and China and local communities. Coastal cities such as Samudra Pasai and Malacca became centers for the spread of Islam, which then spread to other regions in the archipelago through trade, missionary and marriage networks. The influence of Islam is not only visible in religious aspects, but also in the development of literature, law and politics. Islamic kingdoms such as Demak, Aceh and Mataram played a significant role in the formation of Islamic identity and culture in this region. In addition, Islam Nusantara developed with its unique characteristics, combining Islamic teachings with local traditions, which resulted in religious practices that were different from their place of origin. Using historical and sociological approaches to understand how Islam was received and integrated in the local context and its impact on social and political dynamics in the region.